1998
DOI: 10.1258/0956462981921756
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of HIV-1 and HIV-2 infection in urban and rural areas in Tamil Nadu, India

Abstract: We aim to study the factors associated with the prevalence of HIV-1 and HIV-2 infection in the urban and rural areas of Tamil Nadu, India. The population of Tamil Nadu is approximately 60 million. Between April 94 and March 95, 992 samples from 5 representative urban centres and 1071 samples from 5 representative rural centres were collected and studied. A questionnaire was administered privately and it preceded collection of each sample. Samples were screened using ELISA and antibodies to HIV-1 and HIV-2 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 9 publications
2
48
1
Order By: Relevance
“…[6] Heterosexual contact was the commonest mode of transmission (54.75%) of all HIV cases and is consistent with other studies in India. [7,8] This study also showed an increase in heterosexual route of transmission from 48.22% in 2009 to 60.62% in 2012. IDU once a major cause of HIV in Manipur was the second most common cause of HIV comprising 36.33% of all HIV infection showing gradual decline with from 42.44% in 2009 to 30.97% in 2012.Thus from our study we found that there was a shifting trend from IDU (once the major cause of HIV) to sexual route.…”
Section: Resultsmentioning
confidence: 53%
“…[6] Heterosexual contact was the commonest mode of transmission (54.75%) of all HIV cases and is consistent with other studies in India. [7,8] This study also showed an increase in heterosexual route of transmission from 48.22% in 2009 to 60.62% in 2012. IDU once a major cause of HIV in Manipur was the second most common cause of HIV comprising 36.33% of all HIV infection showing gradual decline with from 42.44% in 2009 to 30.97% in 2012.Thus from our study we found that there was a shifting trend from IDU (once the major cause of HIV) to sexual route.…”
Section: Resultsmentioning
confidence: 53%
“…Murugan and Amburajan observed a prevalence of 0.29% of HIV-2 in south Tamil Nadu, and Solomon et, al. reported a prevalence rate of 0.9% with HIV-2 among urban population [11,12] There are various reports of HIV -2 infection from South India but data from North India is much limited. It was seen that more discordant couples exist with HIV-2 infection than HIV-1 infection as was seen in our case and his spouse in spite of having regular unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
“…India is in the phase of rapidly rising prevalence of HIV with an estimated 4 million cases. Most cases in India are reported from Moombai (Bombay), the largest seaport, Pune (near Moombai), Tamil Nadu, the south coastal province, and Manipur, the province bordered by Myanmar [10][11][12][13] . However, the number of cases varied from none to an increasing figure in other states [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that approximately 12% of CSWs from Bangladesh crossed the border into India and engaged in prostitution in Calcutta 21 . A very low rate of condom usage (1% to 21%) among the clients of CSWs, and the low literacy of CSWs were observed as being risk factors for the transmission of HIV and other STDs in several studies 6,7,12,21,22 . Among the long-distance truck drivers in our survey, 60% had sex with CSWs at least twice a month, and they almost always had sex without using a condom.…”
Section: Discussionmentioning
confidence: 99%